The impacts of the reading environment on EFL reading comprehension: Insights from university student and teacher perceptions - Hoa, Ngo Huong; Ngoc, Tran Thi Kim (Technium Social Sciences Journal, 2026)
This study investigated the impacts of reading environment on EFL students’ reading comprehension. The study involved 129 English-majored students and 19 English teachers who participated voluntarily by completing questionnaires and interviews. The findings reveal that reading environment plays a significant role in shaping learners’ comprehension. Specifically, EFL students report experiencing greater difficulty in comprehension when situated in unorganized or uncontrolled environments regardless of their comfort level in those settings. In contrast, students achieve higher comprehension when reading in quiet, structured, and distraction-free environments such as classrooms, libraries, and examination settings. Interestingly, even students with a high interest in reading are more negatively affected by poor reading environments, suggesting that motivation alone does not mitigate environmental distractions. The study also found a misalignment between teaching practices and students’ environmental preferences, with many teachers encouraging group or pair reading, which can inadvertently increase noise and reduce focus. While teachers generally maintain a quiet atmosphere during reading activities, the need for more designated quiet reading spaces remains critical. These results underscore the importance of environmental design in EFL instruction to provide students with optimal conditions for reading comprehension. The study recommends that teachers prioritize individual reading in quiet settings.